Medical genetics an integrated approach - Schaefer, G. Bradley; Thompson, James N. (McGraw-Hill Education, 2014)
Medical Genetics is the first text to focus on the everyday application of genetic assessment and its diagnostic, therapeutic, and preventive implications in clinical practice. It is intended to be a text that you can use throughout medical school and refer back to when questions arise during residency and, eventually, practice. Medical Genetics is written as a narrative where each chapter builds upon the foundation laid by previous ones. Chapters can also be used as stand-alone learning aids for specific topics. Taken as a whole, this timely book delivers a complete overview of genetics in medicine.--Back cover.